THE EFFECTIVENESS OF INTUITIVE-IMITATIVE APPROACH FOR TEACHING ENGLISH PRONUNCIATION IN INDONESIA VOCATIONAL HIGH SCHOOL - Annisa Shofa Tsuraya (Universitas Islam Negeri Alauddin Makassar, 2020)
Pronunciation involves far more than individual sounds. Word stress, sentence stress, intonation, and word linking all influence the sound of spoken English, not to mention the way we often slur words and phrases together in casual speech. English pronunciation involves too many complexities for learners to strive for a complete elimination of accent, but improving pronunciation will boost self-esteem, facilitate communication, and possibly lead to a better job or least much respect in the workplace. This research aimed at investigating the effect of Intuitive-Imitative Approach in teaching pronunciation. The participants of this research were the second-year students of Indonesia Vocational High School in amount of 40 students. This research applied pre-experimental method. The instruments of this research were pre-test and post-test in oral test. The result of this research finally showed that the students’ pronunciation of post-test score was higher than the students’ pre-test score. Meanwhile, the result of t-test showed that the difference was significant where value of the t-test was greater than the value of the t-table (20.17 ≥ 2.069). Thus, it can be concluded that the use of Intuitive-Imitative Approach is effective to use in teaching pronunciation. So that, by applying this method in learning pronunciation, the teacher are hoped to be more creative to enrich their selected word by choosing the unique words to stimulate students and present them an enjoyable, relax, and understandable way in learning process.